The family Stratiomyidae in Egypt and Saudi Arabia (Diptera: Stratiomyoidea) - El-Hawagry, Magdi (Biodivers Data J, 2021)
BACKGROUND: This study systematically catalogues all known taxa of the family Stratiomyidae in Egypt and Saudi Arabia. It is one in a series of planned studies aiming to catalogue the whole order in both countries. NEW INFORMATION: Twenty species, belonging to seven genera and three subfamilies (Pachygastrinae, Stratiomyinae and Nemotelinae), are treated. One of these genera, Oplodontha and two species, Oplodontha pulchriceps Loew and Oxycera turcica Üstüner & Hasbenli, are recorded herein for the first time from Saudi Arabia. A lectotype for Nemotelus matrouhensis Mohammad et al., 2009 is designated. An updated classification, synonymies, type localities, world and local distributions, dates of collection and some coloured photographs are provided.